Broadcast spawning pattern of acropora cytherea and acropora clathrata from inshore reef area in Kuantan coastal region - Hanapiah, Muhammad Faiz; Saad, Shahbudin; Ahmad, Zuhairi (Kulliyyah of Science, 2019)
Acropora sp. is the second-most abundant of coral genera in Kuantan coastal region (KCR) which located at the east coast of Peninsular Malaysia. This study investigated the timing of coral spawning of two Acropora species; Acropora cytherea and Acropora clathrata through dissection and histological analyses of coral fragments that were collected during predicted spawning months (March until May 2018) from Balok reef, Kuantan. Histological results showed the presence of mature oocytes from sample collected in April and May 2018 which indicate extended gamete release pattern for these species within KCR. The gamete maturity coincided with the peak sea surface temperature within KCR from April until May. To confirm our prediction, intense coral spawning survey was conducted in Raja Muda reef from 7 days before and 12 nights after full moon (NAFM) in April 2019. Acropora cytherea spawned approximately 9- 10 NAFM while Acropora clatharata spawned between 10-11 NAFM. The onset of spawning for KCR was delayed about a week compared to previously reported coral spawning in Tioman Island. This study contribute to the limited knowledge of coral reproductive biology in the east coast of Peninsular Malaysia. In addition, the timing of coral spawning provides valuable data for population connectivity modelling.